Numerical analysis of marine propellers low frequency noise during maneuvering. Part II: Passive and active noise control strategies. (August 2022) - Dubbioso, Giulio; Muscari, Roberto; Ortolani, Fabrizio; Di Mascio, Andrea
Abstract: Maneuvering motion inevitably modifies the acoustic signature of marine propellers due to alteration of the wake field past the hull. This aspect is crucial to fulfill the stringent requirements for the noise abatement in the environment. Therefore, design procedures, mainly targeted to rectilinear motion in calm water, should encompass these conditions for achieving a low emission profile. In the present work, the analysis presented in Dubbioso et al., (2020) on the noise generated by a marine propeller in behind-hull is contextualized for the development of holistic tools for design and mission planning, with attention to both passive and active noise control strategies. Passive solutions consist of modification of stern appendages and inversion of propeller rotational direction, while active control is implemented by limiting of the absorbed power, load fluctuation and their combination. The noise sources are first computed by a non-interacting R A N S – B E M T procedure and given as input to the acoustic analogy based on the Formulation 1A by Farassat. The test case is a modern twin screw ship undergoing rectilinear advance and turning maneuvers at two different rudder angles for a moderate speed at F N = 0 . 265 .